2019
DOI: 10.1371/journal.pone.0222575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salbutamol and phlorizin on acute pulmonary inflammation and disease severity in experimental sepsis

Abstract: Respiratory infection can be exacerbated by the high glucose concentration in the airway surface liquid (ASL). We investigated the effects of salbutamol and phlorizin on the pulmonary function, oxidative stress levels and SGLT1 activity in lung, pulmonary histopathological damages and survival rates of rats with sepsis. Sepsis was induced by cecal ligation and puncture surgery (CLP). Twenty-four hours after surgery, CLP rats were intranasally treated with saline, salbutamol or phlorizin. After 2 hours, animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…A growing body of evidences have revealed the effects of β2-agonists on possessing anti-inflammatory properties on airways and reducing pro-inflammatory mediators as well as preventing tissue oedema and exudate. Despite sufficient researches have demonstrated the compelling protective effects of salbutamol and other β2-agonists on preventing sepsis in pre-clinical experiments, these agents have not been shown to improve outcomes in clinical trials in ARDS (a syndrome in critically ill sepsis)[26][27]. As we acknowledged, two enantiomers of salbutamol exhibit differential pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidences have revealed the effects of β2-agonists on possessing anti-inflammatory properties on airways and reducing pro-inflammatory mediators as well as preventing tissue oedema and exudate. Despite sufficient researches have demonstrated the compelling protective effects of salbutamol and other β2-agonists on preventing sepsis in pre-clinical experiments, these agents have not been shown to improve outcomes in clinical trials in ARDS (a syndrome in critically ill sepsis)[26][27]. As we acknowledged, two enantiomers of salbutamol exhibit differential pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…We also have previously demonstrated the increase of ASL glucose concentration promoted by SGLT1 inhibitors in the lungs of diabetic animals ( Oliveira et al, 2016 ); however, the opposite effect on ASL glucose concentration was observed under the beta-adrenergic agonist application due to the SGLT1 translocation to plasma membrane of type I and type II pneumocytes. In this context, we also showed that SGLT1 inhibitors promote bronchial inflammation (interferon-γ and Interleucin-1β), reduction on antioxidant system, and atelectasis associated with significant decrease in survival rate in an ARDS promoted by cecum ligation and puncture (CLP)-induced sepsis animal model ( Cardoso-Sousa et al, 2019 ). Otherwise, a specific β2-adrenergic agonist reduced bronchial inflammation (interleucin-1β), preserved higher levels of antioxidant system, and reduced pulmonary atelectasis associated with bronchodilation ( Cardoso-Sousa et al, 2019 ).…”
Section: Pathophysiology Of Dm In Lungmentioning
confidence: 92%
“…In this context, we also showed that SGLT1 inhibitors promote bronchial inflammation (interferon-γ and Interleucin-1β), reduction on antioxidant system, and atelectasis associated with significant decrease in survival rate in an ARDS promoted by cecum ligation and puncture (CLP)-induced sepsis animal model ( Cardoso-Sousa et al, 2019 ). Otherwise, a specific β2-adrenergic agonist reduced bronchial inflammation (interleucin-1β), preserved higher levels of antioxidant system, and reduced pulmonary atelectasis associated with bronchodilation ( Cardoso-Sousa et al, 2019 ). The SGLT1-triggered water transport is feasible directly together with classical Na + and glucose transport, and also indirectly as a powerful facilitator of passive water cotransport ( Erokhova et al, 2016 ).…”
Section: Pathophysiology Of Dm In Lungmentioning
confidence: 92%
See 1 more Smart Citation
“…6 In support of the perspective that SGLT1 might be implicated in the metabolic disarrangement observed in some patients with COVID-19, Dai et al 10 phlorizin was correlated with a decreased survival rate in a rat model of bronchial inflammation and sepsis. 12 SGLT activation has recently been a key therapeutic target in T2D, where excessive glucose reabsorption by the kidneys is observed. 13 Available drugs mainly inhibit SGLT2, located in the early segment of the proximal renal tube, thus leading to reduced renal glucose reabsorption.…”
Section: Hypothesismentioning
confidence: 99%